Ural cohort of the population exposed in childhood - S. A. Shalaginov; L. Yu. Krestinina (Радиационная гигиена)
The object of the study is the cohort of individuals exposed in the Southern Urals in the 1950s at the age of 0–19 years. The relevance of the creation of the cohort of individuals exposed in childhood and adolescence is determined by their high sensitivity to radiation exposure and is associated with the need for differentiated assessments of the radiation risk of morbidity and mortality for individuals exposed at different stages of ontogenesis. The work includes definition of the cohort, the criteria for inclusion and exclusion from the cohort. According to the data as of 01.01.2019, the created cohort includes 32,461 potential members exposed as a result of living in the riverside villages of the Techa River and on the territory of the East Ural radioactive trace; the follow-up period of the cohort is 70 years (from 1950 to 2019). The cohort has an almost equal number of men and women, includes two ethnic groups (Slavs and Turks), the age range is from 0 to 91 years. The formed cohort can be used to assess the radiogenic risk of cancer and non-cancer morbidity and mortality for the low and medium doses of exposure